Acute and chronic performance enhancement in rowing: a network meta-analytical approach on the effects of nutrition and training - Held, S.; Rappelt, L.; Donath, L. (Sports Medicine, 2023)
Introduction: This systematic review and network meta-analysis assessed via direct and indirect comparison the occurrence and magnitude of effects following different nutritional supplementation strategies and exercise interventions on acute and chronic rowing performance and its surrogates. Methods: PubMed, Web of Science, PsycNET and SPORTDiscus searches were conducted until March 2022 to identify studies that met the following inclusion criteria: (a) controlled trials, (b) rowing performance and its surrogate parameters as outcomes, and (c) peer-reviewed and published in English. Frequentist network meta-analytical approaches were calculated based on standardized mean differences (SMD) using random effects models. Results: 71 studies with 1229 healthy rowers (aged 21.5 ± 3.0 years) were included and two main networks (acute and chronic) with each two subnetworks for nutrition and exercise have been created. Both networks revealed low heterogeneity and non-significant inconsistency (I2 = 35.0% and Q statistics: p = 0.12). Based on P-score rankings, while caffeine (P-score 84%; SMD 0.43) revealed relevantly favorable effects in terms of acute rowing performance enhancement, whilst prior weight reduction (P-score 10%; SMD - 0.48) and extensive preload (P-score 18%; SMD - 0.34) impaired acute rowing performance. Chronic blood flow restriction training (P-score 96%; SMD 1.26) and the combination of ß-hydroxy-ß-methylbutyrate and creatine (P-score 91%; SMD 1.04) induced remarkably large positive effects, while chronic spirulina (P-score 7%; SMD - 1.05) and black currant (P-score 9%; SMD - 0.88) supplementation revealed impairment effects. Conclusion: Homogeneous and consistent findings from numerous studies indicate that the choice of nutritional supplementation strategy and exercise training regimen are vital for acute and chronic performance enhancement in rowing.